Pelatihan Garnish Sayur Bagi Pemula Untuk Kader Tim Penggerak Pemberdayaan Dan Kesejahteraan Keluarga Desa Wilayut - Risda Lailul Yulfa Fitria; Yusti Sahida Putri; Ernawati Ernawati; Haniyah Haniyah; Rahayu Mardikaningsih; Eli Retnowati; Misbachul Munir; Tri Seno Anjanarko (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2023)
Utilization of Waste Paper Through Recycling and Entrepreneurial SpGarnish includes the art of competition in making decorations from food in the form of fruits and vegetables that have aesthetic value, but can be consumed. Competence in making garnish prioritizes expertise in carving or shaping materials into artistic items that are always evolving. Community service in the form of vegetable garnish training is aimed at increasing the competence of Wilayut Village housewife cadres to improve the economy and welfare for beginners. This training aims to find out (1) efforts to improve the competence of making garnishes, (2) increase the competence of attitudes, knowledge, and skills, (3) training improves the standard of living influences the level of education in the family. The garnish training does not just provide education but the practice of garnish training is prioritized. The garnish competition activities were carried out by involving training methods, in theory and hands-on practice. The results of the Wilayut Village housewife vegetable garnish competition have started from the process of carving tomato, cucumber, carrot vegetables to form a decorative presentation for food. The skill of garnish can be a source of developing a business for beginners.irit Development.